Whither the Philippines in the 21st century? - Severino, Rodolfo C.; Salazar, Lorraine Carlos (Singapore Institute of Southeast Asian Studies, 2007)
Examines contradictory economic and political trends occurring in the Philippines in order to gain a sense of the country's prospects.
Electronic reproduction.
Keywords: Philippines -- Politics and government -- 21st century; Philippines -- Economic conditions -- 21st century; Philippines -- Social conditions -- 21st century